China’s Rural Development Road - Zhang, Xiaoshan. author. aut Link
XI, 245 p. 1 illus.
Keywords: This book systematically reviews the experiences and problems encountered in the development of China’s rural areas over the past three decades since the start of the country’s economic reform. As such, it addresses the most important aspects in terms of China’s rural communities, farmers and agriculture from the perspective of development, such as the agricultural management system, rural land tenure system, rural fiscal and taxation system, financial system, science and technology system, rural governance structure, poverty alleviation, environmental protection, etc. The approach employed combines essential theories, laws, and policy strategies with rural development practice in order to analyze the success stories and lingering problems, to explore the causes of both, and to offer an outlook on the future of rural development.